Making Product Logo and Labeling As Sales Promotion on MSME Traditional Drink “MF” Jakarta Selatan: Pembuatan Logo dan Pelabelan Produk Sebagai Promosi Penjualan Pada UMKM Minuman Tradisional “MF” Jakarta Selatan - Erlita Khrisinta Dewi; Dahliyah Hayati; Nessa Ananda; Monanda Wandita Rini (Yayasan Ahmar Cendekia Indonesia, 2022)
This community service activity was carried out at the MSME Traditional Drink